Giant cell tumor of thyroid cartilage: A diagnostic dilemma on aspiration cytology. Issue 11 (31st July 2021) - Anandani, Garima M.; Yadav, Rajni; Verma, Hitesh; Jain, Deepali; Mathur, Sandeep; Iyer, Venkateswaran K.
Abstract: Giant cell tumor of the larynx is an uncommon entity with only 44 cases reported in the literature. These tumors occur most commonly in the epiphysis of the long bones of female patients in third decade. Here in we report a case of 23 years old male patient who presented with an anterior neck swelling since past 4 months. Ultrasound and computed tomography of neck revealed a heterogenously enhancing lesion involving posteroinferior half of right thyroid cartilage with extension into the extra laryngeal strap muscle and intralaryngeal right true vocal cord and false vocal cord. The findings were suggestive of a neoplastic cartilagenous lesion. A fine needle aspiration of the right anterior neck mass was performed which showed many mononuclear cells along with multinucleated osteoclast type giant cells. No thyroid follicular cells or inflammatory cells were seen. A diagnosis of giant cell tumor of the thyroid cartilage was rendered on cytology. A biopsy was subsequently performed for the patient which confirmed the same. Hence, although giant cell tumor of the larynx is a rare entity, with very few cases reported in the literature, these tumors should be included in the differential diagnosis of giant cell lesions of the neck and aspiration cytology can offer an accurate and quick diagnosis in such cases.